Debate Technique: A Way to Enhance Students’ Speaking Skill - Muhammad Usman; Alan Fadinata; Nurul Fajri; Ulminarika Ulminarika; Rahmatun Maulisa (English LAnguage Study and TEaching, 2020)
One of language skills is speaking. Thus, it needs to be improved through appropriate teaching technique such as Debate; using British Parliamentary System. The population of this study consisted of all students who finished Speaking II and IV courses in the Academic Year of 2014-2015. Seventy-five students were chosen as the sample of this study; 32 students were in the control class and 43 students in were in the experimental class. Then, tests were used in collecting the data. The data were then analyzed by using t-test. The result showed that the students of English Study Program of FKIP USM who were taught speaking skill by using Debate with British Parliamentary System received higher score than those who were taught without implementing Debate British Parliamentary System. Based on the findings, the writers recommend that the lecturers can use Debate technique with British Parliamentary System in teaching speaking to improve students speaking skill.